DETERMINANTS OF CAPITAL STRUCTURE IN THE AGRICULTURAL SECTOR: EMPIRICAL EVIDENCE FROM LISTED COMPANIES - Grujić, Miloš; Vojinović, Željko; Đuričić, Zoran; Šuput, Srđan (Economics of Agriculture, 2024)
This study investigated the capital structure of 18 publicly traded agricultural companies over a 10-year period (2012-2022), specifically focusing on short-term debt to total liabilities (SHTDTL). Employing a dataset of 121 observations, the strategic financing decisions of these firms in the Republic of Srpska’s stock market were analyzed. The study examines the impact of various factors, including total debt to total equity (TDTC), tangible assets (TOA), company size (CS), current assets ratio (CR), current assets to total assets (CAA), return on equity (ROE), and return on assets (ROA), on capital structure choices. Results reveal that TOA, CAA, and ROE significantly positively influence the short-term debt ratio, while CS and ROA have a significant negative impact. This research sheds light on the financial decision-making of agricultural enterprises, offering insights that can inform their financing strategies and improve financial performance.